Globalization and north east India - Deb, Bimal J. (ed.); Sengupta, Keya (ed.); Ray, Datta (ed.) (New Delhi, 2008)
This book having 29 papers presented at a national seminar, organized by the North East India Council for Social Science Research, Shillong, attempts to assess the prospects and constraints facing North East India in absorbing the New Economic Policy in its political economy. Analyzing the implications of New Economic Policy for the development of the North East region, the contributors address a wide range of issues concerning the market-oriented reforms in healthcare delivery system, inclusive growth of North East economy, FDI flow in the region, micro-finance, employment generation, poverty alleviation, resource mobilization, the renewable energy policy, and Look East Policy. They also examine the impact of globalization on society, and economy of the region.